2015
DOI: 10.1111/rda.12599
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Contamination by Zearalenone and Its Metabolites on Serum Anti‐Müllerian Hormone: Impact on the Reproductive Performance of Breeding Cows

Abstract: We investigated the effects of in vivo exposure to low zearalenone levels on the anti-Müllerian hormone endocrine levels and the reproductive performance of cattle. Urine and blood samples and reproductive records were collected from two Japanese Black breeding female cattle herds with dietary zearalenone contamination below the threshold levels (<1 ppm) at 30 days after calving. Urinary zearalenone, α-zearalenol and β-zearalenol concentrations were measured by chromatography-tandem mass spectrometry, and seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…According to Fushimi et al [ 25 ], very low levels of ZEN in feed do not affect reproductive performance, but they affect anti-Müllerian hormone levels in the blood [ 26 , 27 ] which play an important role in folliculogenesis and are most highly expressed in the granulosa cells of preantral follicles, mostly in the antral stage [ 28 , 29 ]. These hormones inhibit follicle stimulating hormone (FSH)-induced growth and development of the remaining primary follicles and the selection of the dominant follicle [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Fushimi et al [ 25 ], very low levels of ZEN in feed do not affect reproductive performance, but they affect anti-Müllerian hormone levels in the blood [ 26 , 27 ] which play an important role in folliculogenesis and are most highly expressed in the granulosa cells of preantral follicles, mostly in the antral stage [ 28 , 29 ]. These hormones inhibit follicle stimulating hormone (FSH)-induced growth and development of the remaining primary follicles and the selection of the dominant follicle [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary exposure to 5.9 mg/kg ZEN altered the ruminal microbiota and decreased rumen pH, but a compensatory increased feed intake was observed in dry cows [137]. When dairy cows were exposed to ZEN at a level below 1 mg/kg, only an altered protein metabolism was observed, but the immune status was not impaired [144]. In Europe, the recommended maximum level of ZEN in the diet is 0.5 mg/kg, and rarely, a total mixed ration (TMR) will achieve more than 5 mg/kg ZEN.…”
Section: Effects Of Fusarium-toxins On Livestock Production Performancementioning
confidence: 92%
“…Although no other parameter related to sperm function or reproductive endocrinology was evaluated by these authors, it was shown that dietary T-2 (another Fusarium mycotoxin) decreases the sperm of bulls [176]. Cows exposed to ZEN at a dose close to 1 mg/kg diet presented an increase in the population of ovarian antral follicles and increased the synthesis of the anti-Müllerian hormone by follicular granulosa cells [144], a characteristic of polycystic ovaries [177]. This hormone is produced by granulosa cells from growing follicles and regulates the recruitment of the quiescent ovarian follicles.…”
Section: Effect Of Fusarium Toxins On Reproductive System 101 In Vivo...mentioning
confidence: 99%
“…In addition, ZEN modulates the activity of both testes and ovaries in mice, swine, and cows [19]. ZEN intake affected ovarian antral follicles, increased infertility, and hyperestrogenism in cows [20,21]. ZEN-exposed gilts showed an increased organ size, an inducement of hyperplasia in the smooth muscles of the corpus uteri, and a decrease in the number of follicles in the cortex and apoptotic cells in the ovaries [22].…”
Section: Introductionmentioning
confidence: 99%